Economic Growth and the Taylor Rule in the Solow-Tobin Model - Zhang, Wei-Bin (Asian Business Review, 2019)
The purpose of this study is to study a relationship between growth and inflation with the Taylor rule. We apply the Taylor rule in modelling behavior of central banks to traditional neoclassical growth monetary Solow-Tobin growth model. The household behavior is described by Zhang’s concept of disposable income and utility function. Money enters in the individual saving portfolio as in the MIU approach. The model is a synthesis of the basic economic mechanisms in the Solow-Tobin model, the money in utility approach, and the Taylor rule. The wealth accumulation is the key determinant of economic growth like in neoclassical growth theory. Money demand is determined by assuming that the utility is affected by money holding. Money supply is indirectly determined by the Taylor rule. We first build the dynamic model and then simulate the model. We also carry out comparative dynamic analysis with regards to different parameters.